Three-dimensional random Voronoi models for simulation of brittle rock damage around underground excavations in laminated ground - Ghazvinian, E; Kalenchuk, KS; Diederichs, MS (Deep Mining 2017: Proceedings of the Eighth International Conference on Deep and High Stress Mining, 2017)
Three-dimensional Voronoi tessellations are utilised to demonstrate the simulation of brittle damage around underground mine excavations. Synthetic rock mass models are developed based on calibrated simulations that have been up-scaled to represent excavation-scale rock mass conditions. Rock mass anisotropy plays a significant role in the stability of underground excavations, and so anisotropic conditions are replicated by implementing the up-scaled laminated grain-based model composed of elongated three-dimensional Voronoi blocks. Models explore the influence of the orientation of anisotropic fabric with respect to the in situ stress tensor to demonstrate the Voronoi-based discrete element method modelling technique for simulation of brittle failure. The numerical results verified the success of this approach in capturing the correct failure mode controlled by fabric-guided fracturing in the walls of deep undergrounds openings.
Keywords: numerical modelling